Marine Survey Methodology Of The Surficial Geology And Morphology Of Northwestern Graham Island - Brian D. Bornhold (International Marine Minerals Society, 1985)
A comprehensive multi-disciplinary marine geological survey of northwestern Graham Island, Queen Charlotte Islands, British Columbia, Canada was conducted by Offshore Survey and Positioning Services Ltd. of Vancouver, B.C. on behalf of the Geological Survey of Canada; Energy, Mines & Resources Canada, Pacific Geoscience Centre, Sidney, B.C. Canada during October 1984 and July 1985. The aim of the survey was to map both the surficial geology and geomorphology in order to identify and evaluate the nature of the nearshore sedimentation and recent tectonics including stability (slumps and scarps) seafloor faults (frequency and displacements) and both the classification and consistency of soil type boundaries and properties. Data was acquired by utilizing conventional indirect applied marine geophysical techniques including side scan sonar, precision echo sounding and complimentary soil sampling. During October 1984 a total of 320 line kilometres of data including 180 soil samples were acquired. During July 1985 a total of 300 line kilometres of data were acquired including 150 soil samples.